PENGARUH KEDALAMAN MUKA AIR TANAH DAN BAHAN ORGANIK TERHADAP KETERSEDIAAN HARA DAN PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq)DI LAHAN GAMBUT - Romadoni Sahputra; Wawan '; Edison Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This studyaims to determinethe effect ofthe depth ofthe ground water leveland thesoilorganic matterand obtainthe combination ofthe depth ofthe ground water levelto the type oforganic matterthat isbestfornutrient availabilityandgrowthof oil palm plantationson peatlands. This research was conductedusing Split PlotDesign, the mainplotisthe depth ofthe water tableandthe subplotis thetreatment oforganic matter. Researchshowsthat thedepth ofthe ground water levelpeatsignificantly affectthe availability of nutrientsammonium(NH4+), nitrate (NO3-), P-available, an increasethat occurred ineachparameterwere observed,treatmentis bestfoundat a depth ofground water level60-70cmcomparedto thedepth ofthe ground water level40 - 50cmand80 - 90cm. Organic matterin thesoilpeatsignificant effect onthe increasein thepH ofthe soil, ammonium(NH4+), the P-available, K-available, the lengthmidrib, the length ofthe childleaves,increasethe width of theleaf, root volumeand weight ofthe roots ofthe plantoil palmeachsignificantly differenttreatmentwithoutorganic matter. TKKSorganic matterproducesthe highest increasecompared toother organic materials. Combination ofgroundwater level60 - 70cmwithorganic materialsTKKSresult in increasedavailability of nutrientsnitrate (NO3-), P-available heavyoil palmplant roots. Keywords: High Watersurfacesoil, nutrient availability, plant growth